Identifying a core outcome set for pulmonary sarcoidosis research – the Foundation for Sarcoidosis Research – Sarcoidosis Clinical OUtcomes Taskforce (SCOUT) - Harman, Nicola L.; Gorst, Sarah L.; Williamson, Paula; Barnathan, Elliot S.; Baughman, Robert P.; Judson, Marc A.; Junk, Heidi; Sullivan, Eugene J.; Victorson, David E.; Walton, Marc K.; Al-Hakim, Tamara; Nabulsi, Hana; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
BackgroundPulmonary sarcoidosis is a rare granulomatous disease of unknown aetiology. Heterogeneity in the outcomes measured in trials of treatment for pulmonary sarcoidosis has impacted on the ability to systematically compare findings, contributing to research inefficiency. The FSR-SCOUT study has aimed to address this heterogeneity by developing a core outcome set that represents a patient and health professional consensus on the most important outcomes to measure in future research for the treatment of pulmonary sarcoidosis.Research design and methodsA systematic review of trial registries, narrative synthesis of published qualitative literature on the patient experience and results of a patient survey contributed to the development of a comprehensive list of outcomes that were rated in a two round online Delphi survey. The Delphi survey was completed by patients/carers and health professionals and the results discussed and ratified at an online consensus meeting.Results259 patients/carers and 51 health professionals completed both rounds of the Delphi survey. A pre-agreed definition of consensus was applied and the results discussed at an online consensus meeting attended by 17 patients and 7 health professionals). Fifteen outcomes, across five domains (physiological/clinical, treatment, resource use, quality of life, and death), reached the definition of consensus and were included in the core outcome set.ConclusionsThe core outcome set represents a patient and health professional consensus on the most important outcomes for pulmonary sarcoidosis research. The use of the core outcome set in future trials, and efforts to validate its components, will enhance the relevance of trials to stakeholders and will increase the opportunity for the research to contribute to evidence synthesis.